2006
DOI: 10.1111/j.1440-1746.2006.04152.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of consent practices for inpatient colonoscopy and endoscopic retrograde cholangiopancreatography at a tertiary referral center

Abstract: Written consent for inpatients undergoing open-access colonoscopy and ERCP is rarely obtained by the proceduralist. There is substantial variability in the information provided to patients. Guidelines are required to ensure best practice in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Although similar findings have been reported in Australia, Europe and North America [4][5][6][7], these variations warrant further examination, as they are likely to influence patients' ability to make informed decisions about the care they receive. This is underlined by the fact that inadequate consent and explanation is often cited as a contributory issue in cases of litigation arising after ERCP [14,15].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although similar findings have been reported in Australia, Europe and North America [4][5][6][7], these variations warrant further examination, as they are likely to influence patients' ability to make informed decisions about the care they receive. This is underlined by the fact that inadequate consent and explanation is often cited as a contributory issue in cases of litigation arising after ERCP [14,15].…”
Section: Discussionsupporting
confidence: 49%
“…Development of quality assurance schemes for endoscopy, such as the Global Rating Scale in the UK [2], in addition to an increased focus on patient satisfaction [3], further emphasizes the importance of patients understanding the risks and benefits of any procedure recommended to them. Although a number of groups, including our own, have examined endoscopists' self-reported ERCP consent practice [4][5][6][7][8], few data are available regarding patients' experiences of ERCP, or their recall of information supplied to them as part of the procedure.…”
Section: Introductionmentioning
confidence: 98%
“…Though asking for informed consent is a crucial step for ensuring a successful ERCP, it is surprising to find out that published literatures on this important issue are quite scarce, and that most existing reports are cross‐sectional surveys of endoscopists . Not only few reports were related to patients but, to the best of our knowledge, no randomized trial aimed at improving patients' understanding of ERCP procedure has ever been reported.…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study demonstrated that the majority of patients was either satisfied or very satisfied with the current informed consent process for colonoscopy, 4 however, there is substantial variability in the information provided to patients 5,6 and many colonoscopists do not provide adequate information to patients. 7-10 A Western Australian audit, 5 for consent practices in colonoscopy, identified that 12% of interns (doctors in their first postgraduate year) did not always mention perforation or hemorrhage and >50% of interns overestimated colonoscopic failure and perforation rates.…”
mentioning
confidence: 99%
“…7-10 A Western Australian audit, 5 for consent practices in colonoscopy, identified that 12% of interns (doctors in their first postgraduate year) did not always mention perforation or hemorrhage and >50% of interns overestimated colonoscopic failure and perforation rates. 5 Determining how much information is required for patients to give informed consent is difficult and there is a paucity of literature to assist in this process. 5 Determining how much information is required for patients to give informed consent is difficult and there is a paucity of literature to assist in this process.…”
mentioning
confidence: 99%